Paternal imprisonment and adolescent boys’ charge rates - Olsen, Rikke Fuglsang (European journal of criminology, 2022)
This study uses Danish registry data on the 1993?6 birth cohorts to examine whether paternal imprisonment affects adolescents? charge rates over and above their fathers? criminality and socioeconomic background factors. The results lend support to an interpretation regarding boys, where paternal imprisonment experienced in adolescence (age 16?18) increases adolescent boys? charge rates if the paternal imprisonment sentence has a duration of more than 30 days. Shorter paternal imprisonment spells did not have an impact on adolescent boys? charge rates. Moreover, and surprisingly, the results also suggested that the charge rates of adolescents who cohabitated with their father prior to imprisonment (a proxy for the closeness of the father?adolescent relationship) were not significantly affected, whereas those adolescents who did not cohabit with their fathers prior to imprisonment were. Sensitivity analyses of the estimates, however, warrant caution in the interpretation of the findings.